Transcriptome and gene expression profile of ovarian follicle tissue of the triatomine bug Rhodnius prolixus - Medeiros, Marcelo N. (2011)
Insect oocytes grow in close association with the ovarian follicular epithelium (OFE), which escorts the oocyte during oogenesis and is responsible for synthesis and secretion of the eggshell. We describe a transcriptome of OFE of the triatomine bug Rhodnius prolixus, a vector of Chagas disease, to increase our knowledge of the role of FE in egg development. Random clones were sequenced from a cDNA library of different stages of follicle development. The transcriptome showed high commitment to transcription, protein synthesis, and secretion. The most abundant cDNA was a secreted (S) small, proline-rich protein with maximal expression in the vitellogenic follicle, suggesting a role in oocyte maturation. We also found Rp45, a chorion protein already described, and a putative chitin-associated cuticle protein that was an eggshell component candidate. Six transcripts coding for proteins related to the unfolded protein response (UPR) by were chosen and their expression analyzed. Surprisingly, transcripts related to UPR showed higher expression during early stages of development and downregulation during late stages, when transcripts coding for S proteins participating in chorion formation were highly expressed. Several transcripts with potential roles in oogenesis and embryo development are also discussed. We propose that intense protein synthesis at the FE results in reticulum stress (RS) and that lowering expression of a set of genes related to cell survival should lead to degeneration of follicular cells at oocyte maturation. This paradoxical suppression of UPR suggests that ovarian follicles may represent an interesting model for studying control of RS and cell survival in professional S cell types.